2022
DOI: 10.3389/fpubh.2022.1029190
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differences in COVID-19 diagnosis, risk factors and disease comorbidities: A large US-based cohort study

Abstract: IntroductionMorbidity and mortality from COVID-19 are higher among men, however, underlying pathways remain controversial. We aim to investigate sex-gender differences in COVID-19 in a large US-based cohort, namely COVID-19 Research Database. More specifically, the objectives are to explore the socio-economic characteristics of COVID-19 male and female patients and to examine potential sex differences in lifestyle factors and disease comorbidities among diagnosed patients.MethodsThis is a retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 41 publications
2
18
1
1
Order By: Relevance
“…Furthermore, males were over-represented in the most critical TGs (TG3/TG4), in line with sex as a risk factor of COVID-19 severity. 23,24 Additionally, our results support Hispanic ethnicity correlating with severity. 25,26 Notably, Hispanics formed a higher percentage of TG3, with higher rates of obesity and cardiovascular/renal comorbidities.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, males were over-represented in the most critical TGs (TG3/TG4), in line with sex as a risk factor of COVID-19 severity. 23,24 Additionally, our results support Hispanic ethnicity correlating with severity. 25,26 Notably, Hispanics formed a higher percentage of TG3, with higher rates of obesity and cardiovascular/renal comorbidities.…”
Section: Discussionsupporting
confidence: 73%
“…We also found that female sex was significantly associated with having an asthma exacerbation in the setting of SARS‐CoV‐2 infection. Though male sex has been associated with increased risk of COVID‐19 morbidity and mortality 33–36 and female sex has been associated with increased risk of long‐COVID symptoms, 37 to our knowledge female sex has not been previously associated with higher risk of COVID‐19‐related asthma exacerbations or acute asthma symptoms. These associations with SARS‐CoV‐2‐related asthma exacerbations should be further investigated in larger, multicenter studies.…”
Section: Discussionmentioning
confidence: 79%
“…While autoimmune disorders are more common among women, men might be more sensitive to hyperinflammatory conditions and might be in higher risk of developing more severe disease. For instance, men have a higher risk of developing severe COVID-19 disease and higher mortality rates [19, 20]. Furthermore, one major form of estrogen, estradiol, has been shown to dampen excessive production of innate inflammatory cytokines produced by macrophages and monocytes [19].…”
Section: Discussionmentioning
confidence: 99%